2021
DOI: 10.1177/2050640620972615
|View full text |Cite
|
Sign up to set email alerts
|

European Registry on Helicobacter pylori management: Single‐capsule bismuth quadruple therapy is effective in real‐world clinical practice

Abstract: Background There has been resurgence in the use of bismuth quadruple therapy (proton pump inhibitor, bismuth, tetracycline and metronidazole) for treating Helicobacter pylori infection thanks to a three-in-one single-capsule formulation. Objective To evaluate the effectiveness and safety of the single-capsule bismuth quadruple therapy. Methods Data were collected in a multicentre, prospective registry of the clinical practice of gastroenterologists on the management of H. pylori infection, where patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 30 publications
4
50
2
2
Order By: Relevance
“…The specific analysis of first-line therapies showed that the single capsule bismuth quadruple, the bismuth-amoxicillin-clarithromycin quadruple, and the non-bismuth concomitant regimen obtained the highest effectiveness, in agreement with previous analyses [ 7 , 33 , 34 ]. Neither of these therapies showed an association between treatment effectiveness and the use of statins.…”
Section: Discussionsupporting
confidence: 88%
“…The specific analysis of first-line therapies showed that the single capsule bismuth quadruple, the bismuth-amoxicillin-clarithromycin quadruple, and the non-bismuth concomitant regimen obtained the highest effectiveness, in agreement with previous analyses [ 7 , 33 , 34 ]. Neither of these therapies showed an association between treatment effectiveness and the use of statins.…”
Section: Discussionsupporting
confidence: 88%
“…All patients with a positive test for Helicobacter pylori underwent effective eradication therapy in accordance with the applicable standards and on the recommendation of the attending physician. However, in most European countries, therapy based on the use of a single capsule of bismuth is indicated and used [34].…”
Section: Discussionmentioning
confidence: 99%
“…Nyssen et al reported large-scale real-world data on more than 2000 people, showing that three-in-one single-capsule bismuth quadruple therapy (BQT) performed well not only in rescue treatments but also in first-line therapy. 5 Although BQT is already recommended as a first-line regimen in regions of high (>15%) dual clarithromycin and metronidazole resistance in the European guidelines Maastricht V/Florence Consensus Report, the level of evidence was low due to lack of large-scale real-world clinical data. 6 From this point of view, their study provides strong evidence supporting the guidelines' recommendation.…”
Section: In This Month's Issue Of United European Gastroenterology Jomentioning
confidence: 99%